The Role of Cytokines, Chemokines, and Growth Factors in the Pathogenesis of Pityriasis Rosea - Drago, Francesco (Mediators Inflamm, 2015)
Introduction. Pityriasis rosea (PR) is an exanthematous disease related to human herpesvirus- (HHV-) 6/7 reactivation. The network of mediators involved in recruiting the infiltrating inflammatory cells has never been studied. Object. To investigate the levels of serum cytokines, growth factors, and chemokines in PR and healthy controls in order to elucidate the PR pathogenesis. Materials and Methods. Interleukin- (IL-) 1, IL-6, IL-17, interferon- (IFN-) γ, tumor necrosis factor- (TNF-) α, vascular endothelial growth factor (VEGF), granulocyte colony stimulating factor (G-CSF), and chemokines, CXCL8 (IL-8) and CXCL10 (IP-10), were measured simultaneously by a multiplex assay in early acute PR patients' sera and healthy controls. Subsequently, sera from PR patients were analysed at 3 different times (0, 15, and 30 days). Results and discussion. Serum levels of IL-17, IFN-γ, VEGF, and IP-10 resulted to be upregulated in PR patients compared to controls. IL-17 has a key role in host defense against pathogens stimulating the release of proinflammatory cytokines/chemokines. IFN-γ has a direct antiviral activity promoting NK cells and virus specific T cells cytotoxicity. VEGF stimulates vasculogenesis and angiogenesis. IP-10 can induce chemotaxis, apoptosis, cell growth, and angiogenesis. Conclusions. Our findings suggest that these inflammatory mediators may modulate PR pathogenesis in synergistic manner.